2001
DOI: 10.1080/09595230120058579
|View full text |Cite
|
Sign up to set email alerts
|

Naltrexone in the treatment of male alcoholics - an effectiveness study in Singapore

Abstract: Naltrexone has been demonstrated in western studies to be a useful pharmacological adjunct within treatment programmes for alcoholic patients. We report the first study of its efficacy and usefulness in an Asian region. This project was designed to allow naltrexone˜s performance to be assessed under routine clinical conditions but with patients selected on the basis of their being likely to comply. Following in-patient detoxification, 53 male alcohol-dependent patients admitted to the Alcohol Treatment Centre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Twenty‐seven studies were identified by the NICE guideline as meeting inclusion criteria . An additional two studies were identified for inclusion in the current review , but one did not report the relevant outcomes and so was excluded for the purposes of this review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty‐seven studies were identified by the NICE guideline as meeting inclusion criteria . An additional two studies were identified for inclusion in the current review , but one did not report the relevant outcomes and so was excluded for the purposes of this review.…”
Section: Resultsmentioning
confidence: 99%
“…It was decided that this methodology was not in accordance with the aims of this review. Therefore, a total of 27 studies were included in the current review that investigated the efficacy of naltrexone for alcohol relapse prevention . A total of 2253 participants in the naltrexone group and 1946 participants in the placebo group were included in the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded four studies not using the double-blindness design (Lee et al, 2001 ;Rubio et al, 2001Rubio et al, , 2002 and a clearly defined diagnostic system (Huang et al, 2002). Twenty-four papers were identified as original articles presenting main findings of 24 RCTs (see Table 1).…”
Section: Study Inclusion and Characteristicsmentioning
confidence: 99%
“…As alcohol intake enhances endogenous opioid activity in the central nervous system, it has been proposed that opioid antagonists like naltrexone reduce the risk of relapse. Up to now, the results of 11 controlled studies with a total of about 1500 patients have been published (23–33). With the exception of the results of two multicenter trials (32,33), the other results revealed a superiority of naltrexone to placebo.…”
Section: Introductionmentioning
confidence: 99%